Práticas e percepções dos educadores infantis sobre o aleitamento materno nos Centros Municipais de Educação Infantil de Foz do Iguaçu - PR - Pereira, Bianca da Silva Alcantara (2016)
Breast milk is the best food for babies in their first four to six months of life. Despite widely publicized by the media and health professionals, keeping exclusive breastfeeding for six months is a challenge. Breastfeeding (BF) is a multifactoral behavior. Thus seeking ways to promote and ensure breastfeeding during this period is a task that can now be defended by the Municipal Centers for Early Childhood Education (CMEI) because health professionals are increasingly taking responsibility for the education, development and growth of children due the strong presence of women in the labor market. The objective of this study is to describe the practices and perceptions of CMEI's early childhood educators on the promotion of breastfeeding. For that purpose, we have designed this exploratory descriptive study of qualitative approach. Participants are early childhood educators working in CMEI's Nursery I in the city of Foz do Iguaçu/PR. Data collection occurred during the months of April, May and June 2015, after approval by the Ethics Committee of the State University of Western Paraná. It was used for the analysis of quantitative data, descriptive statistics and qualitative data, a technique of the Collective Subject Discourse (CSD) proposed by Lèfevre & Lèfevre (2005). The professional profile of Nursery I room is predominantly female, twenty-six year old, over six years of experience, 40-hour workweek, no other employment relations, teaching after over a year of training, with children, having breastfed for less than six months, even having positive experience and no problems with it (BF). They feel the need for continuing education and professional training, especially in first aid. About the infrastructure; all nursery I rooms have lactary with minimum structure required; most of the municipality's rooms do not have solarium or have no sunlight; no institution has breastfeeding room or free entrance to BF or free time for women to breastfeed and most rooms have two teachers for every fourteen students. The construction of the CSDs allowed us to see that female teachers think BF is negative and there are no benefits in this practice for children enrolled in nursery I mainly because of the mother s unwillingness to visit the CMEI. Thus, the site is not considered a good place for the mother to breastfeed. Seven difficulties and no advantage have been identified for this practice in the CMEI; the main reason was the routine of the institution and the difficulty in weaning and adaptation. DSCs point to the perception of childhood educators about BF as a hindrance to their professional practice and therefore the teaching, maintenance and promotion of breastfeeding do not occur within the CMEI, which confirms such reality. The infrastructure does not cooperate in the practice of breastfeeding inside the Municipal Center for Early Childhood Education. It is a landmark for educational activities among these professionals, because knowing educational needs is the first step for a real change in such an important practice for a mother and her child.